1995
DOI: 10.1006/viro.1995.1295
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Response to T-cell Activation by Integrated HIV-1 and HTLV-1 LTR-lacZ Vectors

Abstract: Human Jurkat T-cell clones containing stably integrated HIV-1 LTR or HTLV-1 LTR/lacZ vectors were studied to compare the responses of integrated LTRs to T-cell activation. Responses were compared also with those obtained in parallel with Jurkat cells stably expressing lacZ under the control of the cellular enhancer element NF-AT of the IL-2 promoter. Activation induced via the cell surface TCR/CD3 complex or the CD28 receptor elicited responses from the LTR of HIV-1; however, HTLV-1 LTR-directed expression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…Although we have not yet fully addressed this issue, the absence of possible negative regulatory elements or the spatial reorganization of the TRE repeats in relation to the TATA box might all be plausible explanations for these differences. Transient transfection experiments conducted with a vector carrying mutations in the three TRE sequences indicated that these cis-acting motifs are also important for TCR-CD28-PGE 2 activation is consistent with data from Copeland et al (14). However, our observation that PGE 2 when used alone is a very weak inducer of HTLV-1 transcription in human T cells is in contrast to that of Moriuchi and coworkers (51).…”
Section: Discussionsupporting
confidence: 91%
“…Although we have not yet fully addressed this issue, the absence of possible negative regulatory elements or the spatial reorganization of the TRE repeats in relation to the TATA box might all be plausible explanations for these differences. Transient transfection experiments conducted with a vector carrying mutations in the three TRE sequences indicated that these cis-acting motifs are also important for TCR-CD28-PGE 2 activation is consistent with data from Copeland et al (14). However, our observation that PGE 2 when used alone is a very weak inducer of HTLV-1 transcription in human T cells is in contrast to that of Moriuchi and coworkers (51).…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that antibody-mediated signaling through the TCR⅐CD3 complex activates HIV-1 transcription and co-engagement of CD28 further augmented virus gene expression (3,4). Interestingly, ligation of CD28 alone is sufficient to induce HIV-1 transcription and replication both in Jurkat cells (5) and in naturally infected leukocytes (6).…”
Section: Replication Of Human Immunodeficiency Virus Type-1 (Hiv-1)mentioning
confidence: 99%
“…Because a number of cis-acting motifs located within the HIV-1 LTR are also found in the regulatory region of genes induced after T-cell activation, extracellular signals that mediate T-cell activation and lymphokine gene expression also regulate HIV-1 gene expression. It has been shown that antibody-mediated signaling through the T-cell receptor (TCR)/CD3 complex activates HIV-1 transcription, and coengagement of the costimulatory molecule CD28 further augments virus gene expression (19,47). An increasing number of accessory cell surface molecules are also involved in upregulation of T-cell activation (reviewed in reference 51).…”
mentioning
confidence: 99%